Green Finance and Environmental Pollution: Empirical Evidence from Asia - Dang, Anh (International Journal of Energy Economics and Policy, 2025)
This paper analyzes the impact of green finance on carbon emissions in 12 Asian countries during the period 2014–2024. Green finance is measured through three dimensions: green credit, green investment, and green building, along with control variables such as population density, GDP per capita, economic growth rate, and energy consumption. The results of the fixed-effects model indicate that green credit and green investment have a statistically significant negative relationship with carbon emissions, while green building does not show a clear effect. To quantify the overall impact, a composite green finance index is constructed using the Principal Component Analysis (PCA) method, and the results further confirm the positive role of green finance in reducing environmental pollution. Robustness checks conducted with alternative dependent and independent variables yield consistent results. Based on these findings, the study suggests several policy implications, including the expansion of green credit and green investment, the promotion of renewable energy use, and the establishment of a sustainable green financial system to achieve green development goals across Asia.